2018
DOI: 10.1101/331702
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Published estimates of group differences in multisensory integration are inflated

Abstract: Acknowledgments:We thank Kristen Smith for help in reviewing studies of the McGurk effect. Effect inflation in MSI 2 AbstractA common measure of multisensory integration is the McGurk effect, an illusion in which incongruent auditory and visual speech are integrated to produce an entirely different percept. Published studies report that participants who differ in age, gender, culture, native language, or traits related to neurological or psychiatric disorders also differ in their susceptibility to the McGurk e… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…If there are large differences within groups, as there are known to be for face viewing, then detecting a difference between groups requires a larger sample size than those commonly reported. For instance, to detect a difference between groups of 20% (higher than that reported in the literature) with 80% power, a sample size of 50 participants per group is required [27], larger than nearly all of the studies in the literature. Underpowered studies are problematic in two different ways: they may fail to detect actual differences (type II error) or they may over-estimate the size of the difference due to the existence of the so-called statistical significance filter.…”
Section: Statistical Power and Analysismentioning
confidence: 97%
See 1 more Smart Citation
“…If there are large differences within groups, as there are known to be for face viewing, then detecting a difference between groups requires a larger sample size than those commonly reported. For instance, to detect a difference between groups of 20% (higher than that reported in the literature) with 80% power, a sample size of 50 participants per group is required [27], larger than nearly all of the studies in the literature. Underpowered studies are problematic in two different ways: they may fail to detect actual differences (type II error) or they may over-estimate the size of the difference due to the existence of the so-called statistical significance filter.…”
Section: Statistical Power and Analysismentioning
confidence: 97%
“…Underpowered studies are problematic in two different ways: they may fail to detect actual differences (type II error) or they may over-estimate the size of the difference due to the existence of the so-called statistical significance filter. If many underpowered studies or statistical comparisons are performed and only the significant comparisons are reported, between-group difference can be inflated by as much as 10-fold [27].…”
Section: Statistical Power and Analysismentioning
confidence: 99%
“…We note that gender distributions were not matched across the three participant groups. Based on adult studies, it has been suggested that women have a stronger tendency to bind multisensory signals than men (Barnett‐Cowan et al., 2010; Claypoole & Brill, 2019; Collignon et al., 2010; but see Magnotti & Beauchamp, 2018). However, our results suggests that the adult group, which consisted of slightly more females, showed the smallest prior on common cause, and thus the weakest tendency to bind signals.…”
Section: Discussionmentioning
confidence: 99%
“…On a different note, it should be mentioned, that previous research showed rather large variability in the susceptibility of the McGurk illusion (Magnotti and Beauchamp, 2018;Mallick et al, 2015).…”
Section: The Effect Of Hearing Aid Use On the Mcgurk Illusionmentioning
confidence: 95%
“…Differences in susceptibility were attributed to age, gender, culture or native language (Magnotti and Beauchamp, 2018) but also lip-reading abilities (Brown et al, 2018;Strand et al, 2014). Similarly, high variation for fusion effects have been reported for other audio-visual paradigms as for instance the sound-flash illusion (de Haas et al, 2012).…”
Section: The Effect Of Hearing Aid Use On the Mcgurk Illusionmentioning
confidence: 96%